Investigation of the Effect of Life Kinetic Exercises on Shooting Performance in Women Doing Floor Curling - Yunus Gür; Sekuş Taşkin; Emine Şahin; Cengiz Taşkin (Journal of Educational Issues, 2024)
The aim of this study is to examine the effects of life kinetic exercises on the performance of floor curling athletes. A total of 40 volunteer women, 20 in the experimental group and 20 in the control group, residing in the city center of Gaziantep, aged between 14 and 16 and doing floor curling, participated in the study. Life kinetic exercise was applied to the experimental group for 8 weeks along with floor curling training. On the other hand, only floor curling training was applied to the control group. The data were analyzed in the SPSS package program. The normality analysis of the obtained data was done with the Shapiro-Wilk test. Paired Sample T-Test was used for the comparison of normally distributed data within groups. At the end of the study, statistically significant differences were found in the comparison of the pre-test and post-test values of the experimental group. No significant difference was found in the comparison of the pretest and posttest values of the control group. As a result, it can be said that life kinetic exercises have positive effects on individuals’ quick decision making and also on sportive performance depending on this decision.